Magnetic resonance imaging of cerebrospinal fluid spread in the epidural space and postdural puncture headache in obstetrics: A proof-of-concept study. Issue 7 (July 2021) - Ahmed, Iftikhar; Majeed, Amer; Fernando, Roshan; Hyare, Harpreet; Columb, Malachy; Setty, Thunga
Abstract : BACKGROUND: Currently, performing an epidural blood patch (EBP) for postdural puncture headache (PDPH) remains a subjective clinical decision. An evidence-based protocol may be of value in identifying women at high risk of developing a severe PDPH. OBJECTIVE: To investigate a potential correlation between the extent of CSF spread in the epidural space, as noted on Magnetic Resonance Imaging (MRI), and the likelihood of development of severe PDPH in obstetric patients. DESIGN: A prospective double-blind quasi-observational study. SETTING: Eight tertiary obstetric units, from NHS hospitals. PATIENTS: Parturients with accidental dural puncture (ADP) underwent T1 and T2-weighted MRI scans of the brain and lumbar spine within 48 h after delivery. All women were followed up, daily, for 1 week. MAIN OUTCOME MEASURES: For each woman, a PDPH severity score was calculated using a four-point Verbal Reporting Scale (none = 0, mild = 1, moderate = 2, severe = 3), with additional points awarded for visual, auditory and emetic symptoms. MRIs were reported by a neuroradiologist, blind to the patient details, using a predefined MRI score. RESULTS: Twenty-two parturients were recruited; 86% ( n =19) developed PDPH and 10 of these (53%) required an EBP. The median (range) time for the onset of PDPH was 24 (4 to 126) hours. The median (range) cumulative PDPH severity score was 10 (0 to 21), whereas, the median (range) MRI score was 2.5 (0 to 12). Spearman ( r s ) analysis identified a significant positive correlation ( r s  = 0.46; P  = 0.024) between cumulative PDPH severity and MRI scores. Of all the radiological features identified in an MRI (lumbar dural shift, caudal brain displacement, epidural or intrathecal blood), the presence of intrathecal blood was most strongly correlated with PDPH severity ( P  = 0.043). CONCLUSION: Following an ADP, the extent of CSF spread in the epidural space correlates with the severity of subsequent PDPH. CLINICAL TRIAL NUMBER AND REGISTRY URL: ISRCTN14959004, https://www.isrctn.com/ . Abstract : Supplemental Digital Content is available in the text